State of the art advancement in rational design of g-C3N4 photocatalyst for efficient solar fuel transformation, environmental decontamination and future perspectives. (5th March 2022) - Hayat, Asif; Shah Syed, Jawad Ali; Al-Sehemi, Abdullah G.; El-Nasser, Karam S.; Taha, T.A.; Al-Ghamdi, Ahmed A.; Amin, Mohammed A.; Ajmal, Zeeshan; Iqbal, Waseem; Palamanit, Arkom; Medina, D.I.; Nawawi, W.I.; et al.
Abstract: Recently, the graphite based heterogeneous photocatalysts has attained tremendous research attention in various environmental applications. Among them, the graphitic carbon nitride (g-C3 N4 ) is categorized as a unique solar active particle with its outstanding intrinsic properties i.e., adequate band configuration, excellent light absorptivity and thermo-physical durability, which make it highly useful and reliable for revenue transformation and ecological concerns. Considering the intrinsic potential of g-C3 N4 in photocatalysis, so far, no report has been done in literature for its extraordinary configuration, morphological characteristics and perspective tuning for said applications. To overcome this research gap, our primary emphasis of this review regarding photocatalysis is to provide layout as well as the advancement of visible-light-fueled materials as highly stabilized and extremely effective ones for pragmatic implementation. Thus, this existing comprehensive assessment conducts a systematic survey over visible light driven non-metal novel g-C3 N4 . The major advancement of this evaluation is the fabrication of well-designed nanosized g-C3 N4 photocatalysts with unique configurable frameworks and compositions. Furthermore, alternative techniques in order to customize the analogue band configuration and noticeable cultivation such as metal (cation), nonmetal (anion) doping, worthy metal activating, and alloy initiation with certain semiconductors are discussed in detail. In addition to this, g-C3 N4 photocatalytic functionalities towards photocatalytic hydrogen evolution, CO2 photoreduction, biological metal ions deterioration as well as bacterial sanitization are also presented and discussed in detail. Therefore, we believe that such a pivotal compact assessment can provide a roadmap in several perspectives on the currently underway obstacles in the innovation of effective g-C3 N4 catalytic design processes. Moreover, this critical assessment will ultimately serve as a useful supplement in the research area of g-C3 N4 nanosized photocatalysts and for the researchers working on its key aspects in diverse range of natural, chemistry, engineering and environmental applications. Highlights: Graphitic carbon nitride (g-C3 N4 ) is a metal-free sustainable photocatalyst with a band gap of 2.7 eV. G-C3 N4 has improved light absorption performance as well as electronic features. Multiple synthetic approaches are being used with g-C3 N4 to improve its photocatalytic capabilities. Metals/nonmetals doping, activation, and alloy formation are employed for g-C3 N4 nanocomposites. Our review includes the latest current g-C3 N4 nanocomposites and their photocatalytic implications.